Proposta de sistema web para o gerenciamento de escalas de serviço operacional para o corpo de bombeiros militar do Estado do Pará - SOUSA, Luiz Antônio Andrade de (2019)
The State of Pará Military Fire Brigade (CBMPA) is a permanent state body and in fulfillment of the duties assigned to it have units distributed by the state territory. As a way to improve the management processes of the corporation's administrative activities, CBMPA makes use of computational tools (Application Software and Web Applications) developed by State Management Units or by the corporation itself, designed to achieve information management, administrative and operational resources and services of the corporation. With the evolution of Web Development technologies, which provide the development of more sophisticated Web-based Applications and Systems, CBMPA began investing in the development of an Integrated Management System (IMS) platform using a centralized database that integrates diverse information management systems and service channels of the corporation. In this context, and as a result of the completion of this course, a proposal was made for a WebApps capable of assisting the Personnel Sections of the UBMs in the management of operational service scales, as well as in the military personnel change management. For this, good practice principles were applied to the development of Large Web Applications.